1990
DOI: 10.1152/ajpheart.1990.258.2.h285
|View full text |Cite
|
Sign up to set email alerts
|

Sarcolemmal integrity and metabolic competence of cardiomyocytes under anoxia-reoxygenation

Abstract: In tissue, mechanical cell-to-cell interactions may contribute to cardiomyocyte injury in anoxia-reoxygenation. In the present study, the disturbance of energy metabolism and cell injury were investigated in isolated cardiomyocytes, free of external mechanical constraints. Cardiomyocytes from adult rat, attached to culture dishes, were exposed to 120 min of anoxia and 15 min of reoxygenation in a substrate-free modified Tyrode solution. The energetic state of the cells in anoxia-reoxygenation was characterized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
1
1

Year Published

1990
1990
2009
2009

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(39 citation statements)
references
References 0 publications
3
34
1
1
Order By: Relevance
“…The pathogenic relationship between ATP loss and cell necrosis has long been a matter of controversy (Andreoli, 1989). Our results correlate well with the finding of Siegmund et al (1990) that ATP-depleted anoxic cardiomyocytes did not necessarily leak LDH. In contrast, other investigators have concluded that maintenance of cardiomyocyte ATP content is a prerequisite for sarcolemmal integrity (Higgins and Bailey, 1983;Murphy et al, 1987).…”
Section: -supporting
confidence: 89%
“…The pathogenic relationship between ATP loss and cell necrosis has long been a matter of controversy (Andreoli, 1989). Our results correlate well with the finding of Siegmund et al (1990) that ATP-depleted anoxic cardiomyocytes did not necessarily leak LDH. In contrast, other investigators have concluded that maintenance of cardiomyocyte ATP content is a prerequisite for sarcolemmal integrity (Higgins and Bailey, 1983;Murphy et al, 1987).…”
Section: -supporting
confidence: 89%
“…[12][13][14][15] Na ϩ /K ϩ -ATPase activity is highly dependent on myocardial energy, but previous studies have shown that an inadequate energy recovery cannot satisfactorily explain this impairment in cardiomyocytes showing ATP-dependent hypercontracture. 16,17 The mechanisms of this Na ϩ /K ϩ -ATPase failure during reperfusion and contribution to Ca 2ϩ overload and cell death have not been completely elucidated. Na ϩ /K ϩ -ATPase is a transmembrane heterodimer protein composed of ␣ and ␤ subunits.…”
Section: Abstract-namentioning
confidence: 99%
“…In this buffer the osmolality was reduced to 80 mosmol kg¢ to mimic the magnitude of the trans-sarcolemmal osmotic gradient present during the in situ reperfusion (TranumJensen et al 1987). Previous studies have shown that in the presence of this osmotic stress, hypercontracture induced by reoxygenation results in sarcolemmal rupture (Ruiz-Meana et al 1995, while in its absence most hypercontracted cardiomyocytes retain their sarcolemmal integrity despite hypercontracture (Siegmund et al 1990). Loss of cell integrity was characterized by quantification of lactate dehydrogenase (LDH) leakage from the cells into the incubation medium.…”
Section: Myocyte Isolationmentioning
confidence: 99%